Beatriz at dinner [videorecording (DVD)] - Hayek, Salma, 1966-; Lithgow, John, 1945-; Britton, Connie; Duplass, Jay (Lions Gate Entertainment, 2017)
Beatriz, an immigrant from a poor town in Mexico, has drawn on her innate kindness to build a career as a spiritual health practitioner in Los Angeles. Doug Strutt is a cutthroat, self-satisfied billionaire real estate developer. When these two opposites meet at a dinner party, their worlds collide and neither will ever be the same.